The Internet of Toys: Opportunities and Risks in Early Childhood Education: A Mixed Method Exploratory Study - Najmi, Ali Hassan (Journal of Ecohumanism, 2024)
The Internet of Toys (IoToys) is viewed as a subset of the Internet of Things (IoT) and is being marketed as smart toys connected to the Internet that is introduced to children as everday toys. Despite the prevalence of IoToys and its potential for use in education, there is a noticeable absence of studies that seek to understand female teachers’ perceptions of integrating IoToys into early childhood education (ECE). The purpose of this exploratory mixed method study is to investigate ECE teachers’ perceptions of using IoToys in teaching ECE students, through analyzing qualitative and quantitative data. In the qualitative phase of data collection, semi-structured interviews were used for (8) ECE female teachers to obtain their perceptions of using IoToys in ECE and to determine indicators for constructing the quantitative questionnaire. Quantitative data was collected through a questionnare of (100) ECE teachers; with the aim of supporting the qualitative results of the research. The results showed that qualitative and quantitative analyses were consistent in identifying the most important opportunities and risks of IoToys usage. The opportunities of IoToys use include active interaction and social communication, enhancing 21st century skills, personalized education, and IoToys as a flexible learning environment. The most burning risks identified were privacy and cybersecurity, addiction to and emotional attachment to IoToys, and failure of time management as well.